PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA KEDAI KOPI FEBI JAGAKARSA JAKARTA SELATAN - Ira Rahmawati; Ade Ratnasari (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the partial and simultaneous influence of Promotion and Price on Purchasing Decisions at the Febi Jagakarsa Coffee Shop, South Jakarta. The research method used is a quantitative associative method. The sampling technique used is a probability sampling technique in the form of simple random sampling. The sampling technique used the Slovin formula with a tolerable error limit of 10%, so that a sample of 98 respondents was obtained. Data analysis methods include validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of the research show that promotion has a positive and partially significant effect on purchasing decisions with a coefficient of determination value of 65.6%, and the hypothesis test obtained t count > t table (4.475 > 1.985) or a significance of 0.000 < 0.05. Price also has a positive and partially significant effect on purchasing decisions with a coefficient of determination value of 100% and the hypothesis test t count > t table (3.666 > 1.985) or a significance of 0.000 < 0.05. Promotion and price simultaneously have a significant effect on purchasing decisions with the regression equation Y = 20.947 + 0.377 X1 + 0.914 X2. The coefficient of determination value is 100%. Hypothesis testing shows the calculated F value > F table (9.946 > 3.09).